Implementasi Fungsi Pengawasan DPD RI terhadap Pelaksanaan Otonomi Daerah di Provinsi Bali - I Kadek Arimbawa; Ida Ayu Putu Widiati; A.A Sagung Laksmi Dewi (Warmadewa Press, 2020)
The Regional Representative Council (hereafter called DPD) is one of the top state institutions that is directly elected in the General Election. In general, the members of the Regional Representative Council of the Republic of Indonesia (hereafter called DPD RI) are tasked with bringing up the interests and aspirations of the people in the regions to the central government as well as having the authority to carry out supervision in the regions. Supervision in question is the supervision of the implementation of laws, and the results of DPD supervision are submitted to the House of Representatives (hereafter called DPR) as a material for consideration for follow-up. Based on this background, this research was conducted with the aim of describing how DPD RI's supervisory function mechanism on the implementation of regional autonomy in Bali Province and what obstacles DPD RI faces in supervising regional autonomy in Bali Province. This research was conducted using a normative legal research method with a statutory approach. The results of this study showed that DPD RI oversight function is implemented with three mechanisms, namely the absorption of aspirations in the community, conveying aspirations through the preparation of reports and problem inventory lists, and submission of the results of supervision to DPR. While the obstacles faced by DPD RI in supervising regional autonomy in Bali Province are the weak authority of DPD RI compared to its legitimacy, the cooperation pattern between DPD and related regional government agencies that has not been clearly regulated, and the lack of support and community participation for participate in supervising after the enactment of a law.